Undrained Monotonic and Cyclic Response in Thickened Tailings - Cifuentes, LA; Verdugo, R (Paste 2009: Twelfth International Seminar on Paste and Thickened Tailings, 2009)
A series of tests were performed to characterise the undrained monotonic and cyclic response of integral tailings, using CIU triaxial and isotropically consolidated cyclic triaxial tests at different confining stresses. The samples were obtained from thickened tailings ‘manufactured’ and deposited in the laboratory at 72% concentration of solid particles and from samples prepared through moist tamping. With this data, the influence of the ‘fabric’ or sample preparation on the undrained monotonic and cyclic behaviour of the tailings will be evaluated. Finally, the results indicate that the thickened tailings tested are susceptible to liquefaction.